Sternal cable wires for sternal closure in moderately or extremely obese patients undergoing cardiac surgery - Ata, Yusuf; Aydın, Ufuk; As, Ahmet Kağan; Özsin, Kadir Kaan; Fındık, Orhan; Türk, Tamer (The European Research Journal, 2018)
Objectives: Sternal dehiscence is a frequent complication after cardiac surgery. Our study focused on the efficiency of a sternal cable system combined with conventional steel wires for sternal fixation in patients suffering from moderate or extreme obesity and undergoing cardiac surgery. Methods: Prospectively collected data from 22 male and 41 female patients (a mean body mass index [BMI] of 37.9 ± 2.5 kg/m2) who underwent major cardiac surgery via median sternotomy and sternal closure using a multifilament sternal cable system were retrospectively reviewed and analyzed. Results: All patients were closed with a conjunction of two sternal cables and two traditional steel wires. There were two mortalities. There were no occurrences of sternal dehiscence or deep mediastinitis. Three patients suffered superficial sternal wound infections. The mean hospitalization time was 8.4 ± 2.5 days. Conclusion: Our study showed that our surgical technique using a sternal cable system in combination with conventional wires decreased the incidence of sternal dehiscence in moderately and extremely obese patients.